Efeito da temperatura na otimização da produção de glicoproteína do vírus da raiva em cultivos em suspensão de células recombinantes de Drosophila melanogaster S2 - Rossi, Nickeli (Universidade Federal de São Carlos, 2008)
The increment of the expression of complex correctly processed recombinant proteins, like the ones produced by animal cells, is essential for the development of an efficient large scale bioprocess. The manipulation of culture conditions plays a very important role in the controlled and optimized expression of these proteins in bioreactors. The response of mammalian and insect cells to temperature effect has been studied by several researchers as a potential strategy to enhance production of recombinant proteins. The present study evaluated the influence of the temperature in the culture of recombinant Drosophila melanogaster S2 cells in Sf-900 II medium supplemented with aminoacids with the aim of enhancing the production of the rabies virus glycoprotein (RVGP). The cultures were carried out in Schott flasks (in shaker) as well as in a bubble-free stirred tank bioreactor. Five temperatures were tested in Schott flasks cultures: 16, 20, 24, 28 and 34ºC. The results obtained in cultures at those temperatures in terms of maximum specific growth rate (µmax) and maximum RVGP concentration (CGPV max) were, respectively: 0.009, 0.020, 0.039, 0.036 and 0.022 h-1, and 0.075, 2.973, 0.480, 1.404 and 0.013 mg.mL-1. The best temperature for RVGP production (20oC) was chosen to be evaluated in the bioreactor operated in batch and feed-batch mode, keeping 28oC as control. The results of µmax and CGPV max in batch mode were: 0,061 h-1 and 0,149 mg.mL-1 at 28oC and 0,027 h-1 and 0.354 mg.mL-1 at 20oC. A batch experiment with stepwise temperature decrease from 20ºC to 16ºC presented a µmax ranging from 0.024 to 0.012 h-1 and a final CGPV max of 0.567 mg.mL-1. On the other hand, at 20ºC in feed-batch mode, µmax was 0.024 h-1 and CGPV max 1.155 mg.mL-1. The larger production of RVGP observed in Schott flasks can be a consequence of a more favorable condition for the expression of the protein at low values of dissolved oxygen concentrations that are seen in flasks but not in controlled bioreactor cultures at 50% DO. Overall, these results show an increase of recombinant protein expression at lower temperatures, especially when µmax is kept fairly low. The largest production of RVGP was obtained in the culture at 20°C in Schott flask when CGPV max was 2.973 mg.mL-1, while the production obtained at the control temperature of 28ºC was only of 1.404 mg.mL-1. Thus, the use of reduced culture temperatures, around 20°C, seems to be the best strategy for the optimization of RVGP production.
Keywords: Baixas temperaturas; Biorreatores; Drosofila melanogaster; Glicoproteína da raiva; ENGENHARIAS::ENGENHARIA QUIMICA